Tinjauan Etika Bisnis Islam Dalam Implementasi Marketing Mix pada Kedai Kopi Afterwork Caffeine Di Surabaya - Mohammad, Dhanisyah; Anwar, Moch. Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2023)
In build a coffee shop business, business people often apply their marketing strategies without regard to Islamic business ethical values. At a well-known coffee shop, one of the coffee shop employees removes the customer's favorite menu to avoid order buildup. This study aims to determine the implementation of the marketing mix marketing strategy at Afterwork Caffeine coffee shops in Surabaya with the view of Islamic Business Ethics. The method used is descriptive qualitative research method with a field research approach, with data collection techniques using observation, interviews, and documentation. Based on the results of the research carried out that the implementation of the marketing mix marketing strategy at the Afterwork Caffeine coffee shop has been carried out by taking into account the seven marketing mix variables. The Afterwork Caffeine coffee shop has also implemented the values of Islamic business ethics which include monotheism, balance, free will, responsibility, and benevolence.